2017
DOI: 10.1039/c6ra25266d
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-isolation and theoretical study of the HXeCCXeH⋯HCCH and HXeCC⋯HCCH complexes

Abstract: We report on the identification of the complexes of two noble-gas hydrides, HXeCCXeH and HXeCC, with acetylene. These complexes were prepared by photolysis (250 nm) and annealing (55-65 K) of HCCH/Xe matrices. The experimentally observed monomer-to-complex shifts of the H-Xe stretching modes of the HXeCCXeH/HCCH (about +17 cm À1) and HXeCC/HCCH complexes (from +20 to +46 cm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Noble-gas hydrides are photolabile species and their photodecomposition helps the identification of relatively weak bands of their complexes. ,, In the present work, a low-pressure mercury lamp (254 nm) was used to decompose the noble-gas hydrides. For matrices containing both H 2 O and CO, the 1590.3 cm –1 band of the HXeOH···CO complex decreases in intensity synchronously with the band of HXeOH monomer (spectra a and b in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Noble-gas hydrides are photolabile species and their photodecomposition helps the identification of relatively weak bands of their complexes. ,, In the present work, a low-pressure mercury lamp (254 nm) was used to decompose the noble-gas hydrides. For matrices containing both H 2 O and CO, the 1590.3 cm –1 band of the HXeOH···CO complex decreases in intensity synchronously with the band of HXeOH monomer (spectra a and b in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the stability and reactivity of oxonium salt [RXe] + Y À depend on the properties of organic group R and anion Y À . Many Xe C compounds have been theoretically predicted and experimentally prepared, such as C 6 F 5 XeZ(Z = F, Cl, CN) [20], C 2 H 3 COONgH(Ng = Ar, Kr, and Xe) [21], HNgC n N [22,23], XRgCO + (X = F, Cl, Rg = Ar, Kr, Xe) [24], NgMCp + (Ng = He Rn, M = Be Ba, and Cp = η 5 C 5 H 5 ) [25], HXeCCXeHÁ Á ÁHCCH [26], OBNgCN (Ng = Kr, Xe, Rn) [27], Ng 2 @C 60 (Ng = He Xe) [28], FNgCF(Ng = Kr, Xe) [29], RXeXeR(R = CN, NC, CCH, BS) [30], and (Ng) n NC + [31] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…During this time, several key works contributed to the development of noble gas chemistry, including Pauling's theoretical prediction of the existence of the noble gas fluorides in 1933 [1], Neil Bartlett's successful synthesis of Xe + [PtF 6 ] − in 1962 [2], and Räsänen's synthesis of HArF using HF photocatalysis in Ng matrix in 2001 [3]. In recent years, many compounds formed by noble gases and various chemical elements have been synthesized experimentally and/or predicted theoretically [3–37]. It seems that noble gases can bond with every element in the periodic table and plug into any bond to form insertion compounds.…”
Section: Introductionmentioning
confidence: 99%